Naturalization of central European plants in North America: species traits, habitats, propagule pressure, residence time. Issue 3 (1st March 2015) - Pyšek, Petr; Manceur, Ameur M.; Alba, Christina; M Gregor, Kirsty F.; Pergl, Jan; Štajerová, Kateřina; Chytrý, Milan; Danihelka, Jiří; Kartesz, John; Klimešová, Jitka; Lučanová, Magdalena; Moravcová, Lenka; et al.
Abstract : The factors that promote invasive behavior in introduced plant species occur across many scales of biological and ecological organization. Factors that act at relatively small scales, for example, the evolution of biological traits associated with invasiveness, scale up to shape species distributions among different climates and habitats, as well as other characteristics linked to invasion, such as attractiveness for cultivation (and by extension propagule pressure). To identify drivers of invasion it is therefore necessary to disentangle the contribution of multiple factors that are interdependent. To this end, we formulated a conceptual model describing the process of invasion of central European species into North America based on a sequence of "drivers." We then used confirmatory path analysis to test whether the conceptual model is supported by a statistical model inferred from a comprehensive database containing 466 species. The path analysis revealed that naturalization of central European plants in North America, in terms of the number of North American regions invaded, most strongly depends on residence time in the invaded range and the number of habitats occupied by species in their native range. In addition to the confirmatory path analysis, we identified the effects of various biological traits on several important drivers of the conceptualized invasion process. The data supported a model that included indirect effects of biological traits on invasion via their effect on the number of native range habitats occupied and cultivation in the native range. For example, persistent seed banks and longer flowering periods are positively correlated with number of native habitats, while a stress‐tolerant life strategy is negatively correlated with native range cultivation. However, the importance of the biological traits is nearly an order of magnitude less than that of the larger scale drivers and highly dependent on the invasion stage (traits were associated only with native range drivers). This suggests that future research should explicitly link biological traits to the different stages of invasion, and that a failure to consider residence time or characteristics of the native range may seriously overestimate the role of biological traits, which, in turn, may result in spurious predictions of plant invasiveness.